Analysis of Thermal Energy Storage Based on Phase Change of Sugar Alcohol Type Material for Solar Water Heater System - Setiawan, Basuki; Ilham Febriansyah; Ismail (Teknobiz : Jurnal Ilmiah Program Studi Magister Teknik Mesin, 2025)
The increasing use of renewable energy sources as a substitute for fossil energy certainly focuses on the importance of energy storage aspects, especially Latent Heat Thermal Energy Storage. Among a number of Phase Change Materials that can be used in the system, Sugar Alcohol with a high latent heat content and a low to medium temperature range, namely below 140 °C, is suitable for application in Thermal Energy Storage technology, especially Solar Water Heaters. This study tested the thermal performance of Xylitol and Erythritol type Sugar Alcohol, both pure and mixed with composite materials. The use of High-Density Polyethylene as much as 10% and 15% by weight is used as a stabilizer material during the liquid-solid phase change transition. The testing method used in this study uses the Hybrid Energy-Temperature Method, where the sample is heated from ambient temperature to reach a temperature of 150 °C and then cooled to reach ambient temperature again, in the charging/discharging cycle process, to analyze the State of Charge and Depth of Discharging of the tested sample. This study also uses the Differential Scanning Calorimetry method and the Heat Capacity-isostep method to determine the phase change behavior of the sample and calculate the total energy content of the selected sample.